The factors of selecting langkawi island as a tourist destination - Siti Nor Masidayu Mohd Jamil; Siti Noorihan Razali; Siti Nor Sabrina Abd Rahim; Siti Norfatihah Ibrahim (2023)
Malaysia has enlisted many strategies and programs to meet the goal of becoming top 10 positions in the tourism industry. This research has be conduct to know and identify the most influential factors to the tourism industry in Langkawi Island. There are several factors that are enlist as factors to the tourism industry and the results of the research will be proven in the data analysis section. Economical attraction and infrastructure will affect the tourism industry in Langkawi island. The main purpose of this research is to understand and to know the most influential factors of the tourism industry in Langkawi Island.